An analysis of the global burden of childhood and adolescent asthma attributable to high BMI: 1990–2021 - Zhang, Xinhui; Wang, Wen; Wang, Wanqi; Wang, Zhuiyue; Xu, Anran; Xue, Zheng (Frontiers in Pediatrics, 2025)
BackgroundChildhood and adolescent obesity has become a major public health concern, contributing to the increasing burden of asthma. However, the global and regional trends of asthma attributable to high BMI in this population remain unclear. This study aimed to assess the burden of asthma due to high BMI among children and adolescents from 1990 to 2021, exploring disparities across different sex groups and Socio-Demographic Index (SDI) regions and projecting future trends.MethodsData were extracted from the Global Burden of Disease (GBD) 2021 database. The analysis in this study covers the following indicators: age-standardized mortality rate (ASMR), age-standardized disability-adjusted life year rate (ASDR), years lived with disability (YLDs), years of life lost (YLLs), as well as crude mortality rate, crude disability-adjusted life year rate, and their respective percentage change (PC) and estimated annual percentage change (EAPC) from 1990 to 2021. Inequality in disease burden across SDI regions was quantified using the Slope Index of Inequality (SII) and Concentration Index (CI). Future burden projections were conducted using the Autoregressive Integrated Moving Average (ARIMA) model. The percentage of DALYs attributable to risk factors is reported among all age groups and individuals under 20 years.ResultsFrom 1990 to 2021, globally, the mortality rates and numbers of asthma cases caused by high body mass index (BMI) decreased, while the numbers and rates of disability-adjusted life years (DALYs) increased. The number and rate of DALY showed different trends in SDI regions and sex groups. Statistical analysis showed a significant correlation between SDI and asthma burden (P < 0.001), with the overall disease burden increasing as SDI rose. However, this trend was not entirely consistent, as country variations were observed. Otherwise the higher the SDI, the lower the age-standardized mortality rate of asthma usually is. Future projections show that without effective intervention measures, the absolute burden will continue to increase.ConclusionDespite regional differences, the global burden of asthma attributable to high BMI among children and adolescents remains substantial, with notable disparities across SDI regions. Given the projected increase in burden, urgent public health strategies targeting childhood obesity prevention and early intervention are essential to mitigate the long-term respiratory health consequences.